A model for developing a surgical and anaesthesia safety checklist in reducing surgical morbidity and mortality: A literature review - Handayani Rahmaya Nova; AryadiA M.; Suandika Made; Yudha Magenda Bisma; Surtiningsih (BIO Web of Conferences)
Complications that often occur include patient/procedure/surgery site errors, anaesthesia equipment problems, lack of availability of necessary equipment, unexpected blood loss, unsterile equipment, and surgical objects left inside the patient. A surgical checklist can prevent errors and complications that may occur during surgery or perioperatively. The objective is to ascertain the various models of surgical and a naesthesia patient safety checklist instrument and their development. This will facilitate the improvement of compliance with critical patient care in surgical cases through the implementation of surgical and anaesthesia patient safety checklist instruments. This research is a review of related literature and a and a comprehensive study of relevant phenomena. Search and collect literature using the Google Chrome search engine with the keywords Surgical and Anesthesia Patient Safety Checklist. Selection and review adhered to Preferred Reporting Items for Systematic Reviews guidelines. The final review analysis included 25 articles that will be analysed in this review. No significant differences were found regarding morbidity, but there were complications such as infection, bleeding, stroke, and other complications. This study also found that 27.1% of patients did not receive surgical safety checklist training, highlighting the importance of training in patient safety and the use of surgical safety checklists to improve safety and effectiveness in dealing with complications and quality of care. Implementation of a surgical safety checklist increases efficiency, cost reduction, and patient safety. Evaluating and coaching patients before, during, and after procedures is critical to improving patient safety. A surgical safety checklist is important for improving quality and patient safety, but its implementation requires appropriate training programs and the development of patient safety checklists.